Deformation of polyiodides in Cs2I8 crystals at high pressure. Issue 6 (18th November 2021) - Poreba, Tomasz; Garbarino, Gaston; Comboni, Davide; Mezouar, Mohamed
Abstract : Iodine triiodide contacts in zigzag octaiodide units in Cs2 I8 undergo substantial compression, down to intramolecular distances typical for covalently bonded polyiodides. The polyiodide net twists out of its initial shape, allowing for even more expanded connectivity between caesium cations and negatively charged iodine layers. Abstract : Dicaesium octaiodide is composed of layers of zigzag polyiodide units (I8 2− ) intercalated with caesium cations. Each I8 2− unit is built of two triiodides bridged with one diiodine molecules. This system was subjected to compression up to 5.9 GPa under hydrostatic conditions. Pressure alters the supramolecular architecture around I8 2−, leading to bending of the triiodide units away from their energetically preferred geometry ( D ∞h ). Short I2 …I3 − contacts compress significantly, reaching lengths typical for the covalently bonded polyiodides. Unlike in reported structures at ambient conditions, pressure‐induced catenation proceeds without symmetrization of the polyiodides, pointing to a different electron‐transfer mechanism. The structure is shown to be half as compressible [B0 = 12.9 (4) GPa] than the similar CsI3 structure. The high bulk modulus is associated with higher I—I connectivity and a more compact cationic net, than in CsI3 . The small discontinuity in the compressibility trend around 3 GPa suggests formation of more covalent I—I bonds. The potential sources of this discontinuity and its implication on the electronic properties of Cs2 I8 are discussed.